PpcProject: An educational tool for software project management - Salas-Morera, Lorenzo; Arauzo-Azofra, Antonio; García-Hernández, Laura; Palomo-Romero, Juan M.; Hervás-Martínez, César (Computers and education, 2013)
The University degrees about engineering in general, and software engineering in particular, contain subjects related with Project Management. In this subject, the most commonly used software for practical classes and homework is MS-Project. Nevertheless, the students find that MS-Project is not easy to use and that it requires a high knowledge about Project Management and about the use of the software package. To fill this gap, a new educational software tool, called PpcProject, has been developed and introduced in Software Project Management classes in front of MS-Project. When assessed in practical classes, it was shown to be more useful for educational purposes than Microsoft Project both, in terms of usability and of students performance. •MS-Project is not easy to use for educational purposes.•A new software has been developed and introduced in Project Management classes.•Students found that new tool is more usable than MS-Project for learning purposes.•Students got better marks when they used PpcProject than when they used MS-Project.•Future work should be improving the resource allocation module.